A DEVELOPMENT OF PROBLEM-BASED LEARNING ACTIVITY ON THE TOPIC OF ENVIRONMENT AND NATURAL RESOURCE TO ENCOURAGE ABILITY REFLECTIVE THINKING FOR MATTAYOMSUKSA 3 STUDENTS - Nakthong, Minra; Kaewurai, Wareerat (Journal of Buddhist Education and Research (JBER), 2022)
The purposes of this study were 1) to create and find the effectiveness of learning activities, problem-based learning activities on the topic of environment and natural resources to encourage ability of reflective thinking for Mattayomsuksa 3 students according to the criteria 80/80 and 2) to compare the ability of reflective thinking for both pre-study and post-study by using problem–based learning or PBL on the topic of the environment and natural resources for Mathayomsuksa 3 students. The samples of this study were 17 students of Mattayomsuksa 3 of the Bueng Thap Raet School, Lan Krabue District, Kamphaeng Phet Province. The research instruments consisted of PBL activities, 3 learning plans by using PBL on the topic of environment and natural resources to encourage ability of reflective thinking for Mattayomsuksa 3 students, and ability of reflective thinking test. The result of research were as follow: PBL activities consisted of 6 steps. The first step was problem definition by exemplified the surrounding situations, such as forest fire, polluted water, etc. and then question and find the answers. The second step was understanding the problem by brainstorming to find the relevant explanation to problems, such as causes and factors of the problems. The third step was self-study by using various methods for self-directed learning, such as the internet, news, newspapers, magazines, etc. The fourth step was knowledge synthesis by discussion on the solution and perspective. The fifth step was summary and evaluation of the answers. The final step was presentation and evaluation by evaluating the suitable of learning activities. The score was highlevel, respectively ( = 4.49, S.D. = 0.53) and effective at 81.19 / 80.94. The ability of reflective thinking post-study by using PBL activities on the topic of environment and natural resources is higher than pre-study with the significance level of .05